Childhood glaucoma in Down syndrome: a case report and literature review - Raman, Puspha; Subrayan, Visvaraja (International Journal of Contemporary Pediatrics, 2017)
Children with down syndrome have a higher prevalence of glaucoma compared to the age matched normal population. Although the management of childhood glaucoma in a down syndrome child is almost similar to primary congenital glaucoma, the outcomes and prognosis of these children vary due to the associated comorbidities. This case illustrates a classical presentation of a 5-month infant with down syndrome with clinical triad of photophobia, blepharospasm, and epiphora. Prompt recognition of the condition and timely surgical management was vision saving in this child. Extended care for visual rehabilitation was given to this child to maintain the visual outcome.